Elimination of construction contract wastes for enriching the infra-structural development of Bangladesh - Razzaque, Md. Abdur (Brac University, 2021)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2021.